Smoothed-strain approach to topology optimization – a numerical study for optimal control parameters. Issue 5 (11th September 2021) - Lee, Changkye; Natarajan, Sundararajan; Kee, Seong-Hoon; Yee, Jurng-Jae
Abstract: In this study, three variants of strain smoothing technique, viz. the cell-based, edge-based, and node-based smoothed finite element method, are employed for structural topology optimization. The salient features of the strain smoothing technique are: (i) does not require an explicit form of shape functions and (ii) less sensitive to mesh distortion. Within the proposed framework, the structural materials are modelled as the relative material density powered by the power-law approach. An optimum structural topology is estimated from the condition that minimizes the total strain energy of the structures of interest. The efficacy and the robustness of the strain smoothing technique, when applied to topology optimization, are demonstrated with a few standard benchmark problems. A systematic parametric study is done to find suitable and optimal control parameters for the topology optimization, viz. filter size, tuning parameter, and move limit. The relative performance of different strain smoothing techniques for structural topology optimization is also presented. Graphical Abstract: